1995
DOI: 10.1017/s0022112095003582
|View full text |Cite
|
Sign up to set email alerts
|

Geometric focusing of internal waves

Abstract: The spatial structure of the streamfunction field of free, linear internal waves in a two-dimensional basin is governed by the canonical, second-order, hyperbolic equation on a closed domain. Its solution can be determined explicitly for some simple shapes of the basin. It consists of an algorithm by which ‘webs’ of uniquely related characteristics can be constructed and the prescription of one (independent) value of a field variable, related to the streamfunction, on each of these webs. The geometric construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
249
1
7

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(270 citation statements)
references
References 29 publications
13
249
1
7
Order By: Relevance
“…9. different depths at each ITEX2 along-canyon station suggests that the internal tide during this period is standing along the characteristic, in the manner of the basin internal seiches depicted in Maas and Lam (1995). This pattern is seen clearly in Fig.…”
Section: Volume 28 J O U R N a L O F P H Y S I C A L O C E A N O G R mentioning
confidence: 76%
See 1 more Smart Citation
“…9. different depths at each ITEX2 along-canyon station suggests that the internal tide during this period is standing along the characteristic, in the manner of the basin internal seiches depicted in Maas and Lam (1995). This pattern is seen clearly in Fig.…”
Section: Volume 28 J O U R N a L O F P H Y S I C A L O C E A N O G R mentioning
confidence: 76%
“…Internal seiches in basins have been the subject of recent studies (Maas and Lam 1995;Münnich 1996), but they have rarely been observed in the ocean. Niiler (1968) discusses a seiching internal tide in the Straits of Florida, Winant and Bratkovich (1981) identify internal tides standing in the cross-shelf plane on the narrow southern California shelf, and Griffin and Middleton (1992) discuss standing internal wave patterns in the nearshore region off Sydney, Australia.…”
Section: A Possible Internal Tide Generation Sitesmentioning
confidence: 99%
“…Recent observations and more complex models support Munk's inference (Garrett 1991;Toole et al 1994;Ledwell and Hickey 1995;Lueck and Mudge 1997). Processes causing mixing at lateral boundaries include internal waves shoaling at the sediment-water interface, shear from the upward and downward movement of the pycnocline, geometric focusing of internal waves, and flow over topographic features (Ericksen 1982(Ericksen , 1985(Ericksen , 1998Thorpe 1987Thorpe , 1995Taylor 1993;Imberger 1994;Ivey et al 1995;Maas and Lam 1995). Enhanced mixing has also been observed in deep basins when the topography is rough .…”
mentioning
confidence: 86%
“…New interest into the singular solutions to the Poincaré equation was put forward with the work of Maas & Lam (1995) on gravity modes in two-dimensional basins. The pressure fluctuations of internal gravity modes also satisfy Poincaré equation, and Maas & Lam (1995) showed the crucial role of characteristic trajectories and coined the concept of attractor to describe the convergence of characteristics to special limit cycles.…”
Section: Introductionmentioning
confidence: 99%
“…The pressure fluctuations of internal gravity modes also satisfy Poincaré equation, and Maas & Lam (1995) showed the crucial role of characteristic trajectories and coined the concept of attractor to describe the convergence of characteristics to special limit cycles. At the same time, Hollerbach & Kerswell (1995) and Kerswell (1995) investigated the internal shear layers spawned by the critical latitude singularity (another singularity different from that of the attractors), in relation with the precession flows of a spherical shell.…”
Section: Introductionmentioning
confidence: 99%